A proposal for system performance evaluation for an ERP knowledge extraction model - Benedetti, Alexandre [UNESP]; Albino, João Pedro [UNESP]; Cavenaghi, Vagner [UNESP] (My University, 2010)
Much has been researched and discussed in the importance played by knowledge in organizations. We are witnessing the establishment of the knowledge economy, but this new economy brings in itself a whole complex system of metrics and evaluations, and cannot be dissociated from it. Due to its importance, the initiatives of knowledge management must be continually assessed on their progress in order to verify whether they are moving towards achieving the goals of success. Thus, good measurement practices should include not only how the organization quantifies its knowledge capital, but also how resources are allocated to supply their growth. Thinking about the aspects listed above, this paper presents an approach to a model for Knowledge extraction using an ERP system, suggesting the establishment of a set of indicators for assessing organizational performance. The objective is to evaluate the implementation of projects of knowledge management and thus observe the general development of the organization.
Keywords: Knowledge assets; knowledge extraction; Knowledge management; Knowledge management systems; System performance evaluation